Omani-British Cooperation in the Buraimi Crisis (1952–1955) - Shuaili, Mohammad Al (المجلة العلمیة لکلیة الآداب, 2026)
In 1798, the first political treaty between Oman and Britain was signed, establishing the foundation for the development of bilateral relations across various domains. This agreement laid the groundwork for extensive cooperation between Muscat, the capital of Oman, and London in subsequent years, particularly in the military sector. In 1952, Saudi forces reinitiated military intervention in the Buraimi region, located in northwestern Oman, after an absence of more than eighty years, posing a direct threat to the sovereignty and territorial integrity of Oman. This incursion prompted the need for coordinated political and military action between Sultan Said bin Taimur (1932–1970) and his ally, Britain, leveraging the longstanding relationship and formal agreements between the two nations to counter the threat and restore stability.Accordingly, this study seeks to examine the nature and dimensions of Omani-British cooperation during the Buraimi Crisis (1952–1955), highlighting the convergence of mutual interests that underpinned the alliance during this critical episode. The study explores the support extended by the British government to Sultan Said in both political and military contexts and frames the crisis within a historical narrative that traces its evolution from inception to resolution. By outlining the various phases of the conflict and emphasizing Britain’s role throughout, the research aims to provide a comprehensive understanding of this pivotal moment in twentieth-century Gulf politics.